Contribuição das tecnologias da indústria 4.0 para a sustentabilidade : uma revisão sistemática - Santos Germano, Aline Xavier dos (Palabra Clave.)
This study is a systematic review and aims to analyze how research on industry 4.0 is contributing to a greater understanding of the effects of the implementation of industry 4.0 on sustainability. This study was done by mapping the existing research, using selection, eligibility and inclusion criteria as the guiding principle of the PRISMA methodology technique (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). The selection of articles in the databases consulted was based on the crossing of the terms "Industry 4.0" and "sustainability". The research brings as results the main challenges for the implementation of technologies related to industry 4.0, among them the lack of technological infrastructure and resources for investment and what the possible benefits for sustainability this implementation can bring, such as the reduction in the consumption of resources at all stages of production, as well as the environmental impacts generated. Through this study it was possible to conclude that despite presenting factors that positively influence the sustainability of companies, the implementation of new technologies for the adoption of the concept of industry 4.0, is still surrounded by risks and challenges and there is a need for further studies that explore and consolidate the results of the fourth industrial revolution.